The effect of mechanical feedback on the learning and retention of selected gymnastics skills Among female students - Abdulqader, Neran Khaleel; Naji, Saif Alaa (Pendidikan Jasmani, Kesehatan, dan Rekreasi Universitas Nahdlatul Ulama Sunan Giri, 2025)
Technological advances in sports have opened up new opportunities to enhance the efficiency of learning motor skills, including gymnastics. This study found that mechanical feedback improves movement accuracy, speeds up the learning process and reduces performance variability compared to traditional methods. The study examined the impact of real-time mechanical feedback on the acquisition and retention of preferred gymnastics skills among students at the College of Physical Education and Sports Science at the University of Baghdad. A quasi-experimental design was used, with 40 students divided into two groups: an experimental group of 20 students who received mechanical feedback and a control group of 20 students who were trained using traditional methods. Data were collected through pre- and post-workout tests, as well as a retention test, to evaluate skill mastery, execution precision, and endurance. The results showed that mechanical feedback significantly improved movement execution and skill retention compared to the control group. In conclusion, technology-based mechanical feedback has the potential to be an effective training tool in sports, supporting improved performance through better motor control. Further research is needed to explore the long-term effects of mechanical feedback and the integration of artificial intelligence technology in training systems, as well as its effect on psychological and cognitive factors such as motivation, focus and athlete confidence.